Individual risk factors associated with SARS-CoV-2 infection during Alpha variant in high-income countries: a systematic review and meta-analysis - Moniz, Marta; Pereira, Sofia; Soares, Patricia; Aguiar, Pedro; Donato, Helena; Leite, Andreia (Frontiers in Public Health, 2024)
Objectives: This study aimed to systematically appraise risk factors associated with SARS-CoV-2 infection in high-income countries during the period of predominance of the Alpha variant (January 2020 to April 2021). Methods: Four electronic databases were used to search observational studies. Literature search, study screening, data extraction and quality assessment were conducted by two authors independently. Meta-analyses were conducted for each risk factor, when appropriate. Results: From 12 094 studies, 27 were included. The larger sample size was 17 288 532 participants, more women were included, and the age range was 18-117 years old. Meta-analyses identified men [Odds Ratio (OR): 1.23, 95% Confidence Interval (CI): 1.97-1.42), non-white ethnicity (OR: 1.63, 95% CI: 1.39-1.91), household number (OR: 1.08, 95% CI: 1.06-1.10), diabetes (OR: 1.22, 95% CI: 1.08-1.37), cancer (OR: 0.82, 95% CI: 0.68-0.98), cardiovascular diseases (OR: 0.92, 95% CI: 0.84-1.00), asthma (OR: 0.83, 95% CI: 0.75-0.92) and ischemic heart disease (OR: 0.82, 95% CI: 0.74-0.91) as associated with SARS-CoV-2 infection. Conclusions: This study indicated several risk factors for SARS-CoV-2 infection. Due to the heterogeneity of the studies included, more studies are needed to understand the factors that increase the risk for SARS-CoV-2 infection.